Konsep Evaluasi dalam Pembelajaran Bahasa Indonesia di SDN Sangiang III Kabupaten Tangerang - Juwanti Ambarwati; Ina Magdalena; Ribkha Nur Eka Chandra; Risti Anggraini (Jurnal Halaqah, 2020)
This study aims to determine the basic concepts of evaluation and their implications in evaluating Indonesian learning. Type of qualitative research. Research site at SDN Sangiang 3. Subjects of teachers and fourth grade students at SDN Sangiang 3. Interview data collection techniques. Research Subjects are teachers who teach Indonesian subjects. Data collection is done through interviews. The steps of data analysis are recording and collecting, reducing, presenting, and verifying. The results of this study indicate that the evaluation is carried out to determine the effectiveness and efficiency of learning conducted, its function is to determine the capacity of educators and students, so that improvements can be made if indeed there are found factors that are not optimal in the learning process.